2020
DOI: 10.1017/s0022377820001312
|View full text |Cite
|
Sign up to set email alerts
|

Self-sustaining sound in collisionless, high-β plasma

Abstract: Using analytical theory and hybrid-kinetic numerical simulations, we demonstrate that, in a collisionless plasma, long-wavelength ion-acoustic waves (IAWs) with amplitudes $\delta n/n_0 \gtrsim 2/\beta$ (where $\beta \gg {1}$ is the ratio of thermal to magnetic pressure) generate sufficient pressure anisotropy to destabilize the plasma to firehose and mirror instabilities. These kinetic instabilities grow rapidly to reduce the pressure anisotropy by pitch… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
2

Relationship

4
5

Authors

Journals

citations
Cited by 22 publications
(42 citation statements)
references
References 62 publications
3
39
0
Order By: Relevance
“…We point out that qualitative differences may be expected the high-beta regime due to the effect of plasma microinstabilities such as the firehose and mirror instabilities, which arise from pressure anisotropy (Kunz et al 2014). In particular, it was recently suggested that these microinstabilities may impede Landau damping of large-scale compressive fluctuations (Kunz et al 2020), which would have consequences on the results described here.…”
Section: Discussionmentioning
confidence: 67%
“…We point out that qualitative differences may be expected the high-beta regime due to the effect of plasma microinstabilities such as the firehose and mirror instabilities, which arise from pressure anisotropy (Kunz et al 2014). In particular, it was recently suggested that these microinstabilities may impede Landau damping of large-scale compressive fluctuations (Kunz et al 2020), which would have consequences on the results described here.…”
Section: Discussionmentioning
confidence: 67%
“…In this picture the exchange between kinetic and magnetic fluctuations happens at relatively large scales in the inertial range. There are also suggestions that magnetic reconnection, and in some situations large scale instabilities, could potentially bypass the cascade and transfer energy directly into the kinetic range and into internal degrees of freedom [79][80][81].…”
Section: Introductionmentioning
confidence: 99%
“…The measured effective mean-free-path and mean proton thermal speed (measured with this data set) gives an effective collision frequency of ν eff = v p th /λ eff mfp = 1.11 ×10 −4 s −1 . The transition frequency, where ν eff ≃ ω can be estimated with ν eff = v p th /λ eff mfp and the ion-acoustic dispersion relation ω IA = k c s , giving the parallel transition wavenumber k trans = v p th /c s λ eff mfp [37,51,65]. Using the wavenumber model (Eq.…”
mentioning
confidence: 99%
“…Effective collisional processes have long been studied theoretically and numerically [3,[68][69][70][71][72][73], but it is an open question as to the relevant role of the various mechanisms [2,[40][41][42][74][75][76]) and how they are activated [65,77,78]. Therefore, further studies are necessary to assess exactly what key physics of weakly collisional plasma leads to the measured effective collisionality, since most astrophysical plasmas, being multi-scale and turbulent, will support effective collision mechanisms [79].…”
mentioning
confidence: 99%